A study of value creation through the use of 3PL and 4PL partners within the white goods manufacturing industry of China's domestic market : a thesis presented in partial fulfillment of the requirements for the degree of Master in Logistics and Supply Chain Management at Massey University, Auckland, New Zealand - Gao, Shengjun (Massey University, 2013)
Purpose – Over recent years many businesses have recognised that there are strong competitive advantages in adopting outsourcing of logistics functions to logistics providers worldwide. The aim of this research is to understand how Chinese white goods manufacturers utilise contract logistics to increase their profitability and customer service level. Design/methodology/approach – An interview-based approach was utilized to collect data from three of the leading Chinese domestic white goods manufacturers in mainland of China in 2011. Within-case study and cross-case study were the data analysis methods used in this study. Findings – Logistics Service Providers (LSP’s) do significantly and directly increase Chinese white goods manufacturers’ logistics performance efficiency and effectiveness, and in turn, increase their profitability, and indirectly increase customer service levels. Research limitations/implications – Findings are based on senior managers’ personal understandings and responses from three selected manufacturers, therefore personal biases and references could have possibly occurred. Due to time and financial limitations, only three manufacturers were selected from the many possible industry providers, so care needs to be taken not to assume that findings will always be completely representative of the industry. Practical implications – Competition in the field of white goods manufacturing has become more intense than ever before. Chinese white goods manufacturers need to spend all its resources on its core businesses, in order to increase competitiveness, and leave non-core business functions to outside contractors such as outsourcing logistics functions to a third party logistics (3PL) provider.
Keywords: Logistics; Supply chain management; Whiteware industry; Business logistics, China; China; Third party logistics; Logistics service providers; White goods manufacturers